Perencanaan Tambang Secara Manual dan Software Micromine Sebagai Pembanding Pada Kapal Keruk 21 Singkep 1 Di Laut Air Kantung, PT Timah (Persero) Tbk - Elisa Elisa; Irvani Irvani; Janiar Pitulima (MINERAL, 2017)
Dredger 21 Singkep 1 is a mean of production offshore tin mining owned PT Timah (Persero) Tbk, which in 2016 is located in the Air Kantung Sea. Before the implementation of the necessary mining mine planning as a guide to provide an overview of work in the field conditions. Mine planning studies considering the economical extraction and analysis of the operations of dredgers by applying two ways; manually which reserves calculations using the Poligon Methods (Area Of Influence) with sea drilling spacing of 100 × 100 m and assisted Software Micromine as a comparasion. Based in the calculation, the value of the break even production of 42 tonnes ore/month and the break even grade of 0,23 kg/m3. Mining in May to October 2017 to continue the old location to the position of excavation to the northwest. Results obtained Idh manual production planning (Content Calculated) 1.263.980 m3, TDH (Tin Calculated) 0,292 kg/m3 and PDH (Production Calculated) 369,69 tonnes, while the calculation of Micromine obtained Idh 1.271.379 m3, Tdh 0,273 kg/m3 and Pdh 347 tonnes. Fault tolerance value 0,58%. Repair manual planning the excavation efficiency is obtained Idh 1.283.847 m3 increased 1,55%, Tdh 0,327 kg/m3 increased 10,7% and Pdh 409,37 tonnes increased 11,85%. Based on the analysis of drill profiles, the most effective method of extracting using combination system, where the overburden excavation with long face method and leaded soil with short face method.